Giacomo Verde’s Archive - Monteverdi, Anna Maria (Mimesis Journal, 2024)
The I_PAD project (Italian Performance Archive in Digital) brings together scholars from two Italian universities (University of Milan and Link University in Rome) as well as the CNR Institute-ISTI (Pisa). It was awarded under the PRIN 2022 call for Research Projects of National Relevance, funded by the Ministry of University and Research (MUR). The project is coordinated by the University of Milan and is centered on the archive of Italian artist Giacomo Verde (1956–2020), who was active in video art, technological performances, and interactive installations. The project's goal is to demonstrate the importance of documenting, monitoring, digitizing, and disseminating the memory of Italian video theater and video art from the 1980s and 1990s.